Large Bowel Obstruction in a Young Woman Simulating a Malignant Neoplasm: A Case Report of Actinomyces Infection. (27th June 2013) - Nissi, R.; Blanco Sequeiros, R. B.; Lappi-Blanco, E.; Karjula, H.; Talvensaari-Mattila, A.
Abstract : Pelvic and intra-abdominal Actinomycosis can be difficult to diagnose preoperatively and it may also mimic many other diseases, including malignancies. We present a patient with pelvic Actinomycosis probably caused by a long-standing intrauterine device (IUD). We emphasize the challenges in diagnostic process and stress that though a rare disease, intra-abdominal Actinomycosis should be suspected in cases with intra-abdominal mass of uncertain etiology. The early recognition may spare the patient from extensive surgical operation.